1954
DOI: 10.1111/j.1469-7998.1954.tb07803.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of variation in the haemoglobin content of Daphnia (Crustacea: Cladocera) in nature

Abstract: Summary.  The haemoglobin content of Daphnia in the ponds studied was found to vary inversely with the oxygen concentration in the water, but not to be proportional to the iron content of the water.  In six ponds Daphnia was found to have a greater haemoglobin concentration in winter than in summer, whereas in one body of water the haemoglobin concentration was greater in summer than in winter.  Haemoglobin may be more concentrated in the blood of one pond‐dwelling species of Daphnia than of another species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1957
1957
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…4C,D). A previous study (Chandler 1954) 2004b). To withstand hypoxia and to inhabit oxygen-poor water layers, Daphnia enhances the synthesis of Hb macromolecules of higher oxygen affinity (Kobayashi and Hoshi 1982;Kobayashi et al 1988;Sell 1998).…”
Section: Discussionmentioning
confidence: 77%
“…4C,D). A previous study (Chandler 1954) 2004b). To withstand hypoxia and to inhabit oxygen-poor water layers, Daphnia enhances the synthesis of Hb macromolecules of higher oxygen affinity (Kobayashi and Hoshi 1982;Kobayashi et al 1988;Sell 1998).…”
Section: Discussionmentioning
confidence: 77%
“…4C,D). A previous study (Chandler 1954) reported increasing Hb concentrations in Daphnia (D. magna, Daphnia pulex, Daphnia obtusa) sampled during the last months of the year, which was discussed in context of environmental hypoxia. Actually, Hb is an essential part of the oxygen transport system of Daphnia (Pirow et al 2001; Paul et al ).…”
Section: Discussionmentioning
confidence: 87%
“…The English surgeon George Chandler (d. 1823) summarized Platner’s description 69 : “a hard eye resisting to the finger…[with] a certain sensation of weight and pain in it;…within the eye hath the colour of the sea: …the pupil is dilated,…because both the vitreous humour and the retina are pressed by the lens, which is much swelled, the faculty of seeing entirely perishes…; they call this disease a glaucoma.” …”
Section: Introductionmentioning
confidence: 99%